Sustainable development goal and trade in Afghanistan (a case of study : ministry of trade) - Zahid, Mohd Edress (My University, 2021)
Sürdürülebilir kalkınma hedefleri (SKH'ler), kaçınılmazlığına ve uzun vadede biriktirdiği devasa yaygınlığa rağmen, çağdaş ilerleme konuşmalarında ana akım bir ifade haline gelmiştir.Afganistan'da, çok sayıda kişi, ilerleme hipotezi ve uygulaması için içerdiği ve çıkarsadığı gibi, önemi ve tarihi hakkında sorular sormaya devam ettikçe, fikir aslında karışık görünmektedir.Çünkü burada SKH adaptasyonundan somut bir sonuç görülmemiştir.Afganistan, komşuları için üstün bir yaşam arayışında önemli zorluklarla karşılaşmaya devam ediyor.Ancak, her şeye rağmen, son yıllarda, Binyıl Kalkınma Hedefleri'ne pek de aşina olmayan rehberler manzara olarak; Afganistan bazı umut verici ve kritik zaferler görünmüştür.Bu Çalışma, Afganistan'daki SKH'lerin öncelikli listesinde nelerin olacağını ve Ticaretin SKH'lerin gerçekleştirilmesine yardımcı olmak için ne yaptığını bulmaya odaklanmıştır.Bu Çalışma Afganistan Ticaret Bakanlığı'nın üst düzey çalışanları arasında anket yöntemiyle yapılmış ve SPSS üzerinde incelenmiştir.Bu araştırmanın sonucu, Ticaretin, coğrafi konumu nedeniyle, kesin, net bir plan, şeffaflık ve taahhütün var olması Afgan hükümetine ve Afgan halkına SKH'lere ulaşmada yardımcı olabileceğini göstermektedir.

Sustainable development goals (SDGs) have become a mainstream expression in contemporary advancement talk. Be that as it may, despite its inescapability and the gigantic prevalence it has accumulated throughout the long term. In Afghanistan, the idea actually appears to be muddled as numerous individuals keep on posing inquiries about its importance and history, just as what it involves and infers for advancement hypothesis and practice. Because no tangible results from SDG adaptation have been seen here. Afghanistan keeps on confronting significant difficulties in its quest for a superior life for its kin. However, notwithstanding everything, in the course of recent years, while immense measure of unfamiliar guides with the Millennium Development Goals as the scenery; Afghanistan has seen some promising and critical victories. The study focused to find what would be in priority list of SDGs in Afghanistan and what does Trade do to help the achievement of the SDGs. The study was conducted through questionnaire among top level employees of Ministry of Trade in Afghanistan and examined on SPSS. The outcome of this research shows that Trade can help Afghan government and Afghan people to achieve SDGs, because of its geographical location, if there be any exact, clear a precise plan, transparency and commitment.
Keywords: Afghanistan; Business; İşletme; sustainable development goals; Sürdürülebilir kalkınma; sürdürülebilir kalkınma hedefleri; Ticaret sustainable development; Trade